2009
DOI: 10.1080/07399330902733281
|View full text |Cite
|
Sign up to set email alerts
|

Trapped in Circle of Threats: Violence Against Sex Workers in Thailand

Abstract: Most researchers studying sex work have focused on the risks of sexually transmitted diseases, predominantly HIV, for sex workers, their clients, and subsequent partners. Violence against these women often goes undocumented and unnoticed. Consequently, few researchers have addressed violence against sex workers, and these few have generated limited evidence about the nature of violence from the sex-worker perspective--especially the street sex worker perspective. In this study, we used qualitative methods to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…Similar findings have been reported from other settings [3,19]. Condom breakage or clients removing the condom during the transaction were the greatest risk for STIs/HIV infections and unintended pregnancy but these problems were difficult to avoid.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings have been reported from other settings [3,19]. Condom breakage or clients removing the condom during the transaction were the greatest risk for STIs/HIV infections and unintended pregnancy but these problems were difficult to avoid.…”
Section: Discussionsupporting
confidence: 86%
“…However, participants perceived these risks as part of their working environment. A lesson learned from Thailand suggested that sex workers experienced violence as a result of social norms, the legal system, and politics, but they were prepared to accept violence as a condition of the working environment [19]. …”
Section: Discussionmentioning
confidence: 99%
“…In the context of IPV, researchers have found that men and women who ascribe to more traditional and inequitable gender norms also justify wife abuse (Speizer 2010;Abramsky et al 2011). Women in these situations are less likely to seek help from abusive partners, and violence therefore goes untreated and unreported (Ratinthorn, Meleis, and Sindhu 2009). Although research suggests inequitable gender norms remain prevalent in many developing countries, a recent study from Tanzania suggests that norms are transitioning as communities desire greater protection from violence against women (Laisser et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, inequitable gender norms, criminalisation and stigmatisation of sex work contribute not only to their increased risk of IPV, but also to the challenges female sex workers encounter for harm reduction, as they are less likely to seek or receive assistance from violent situations (Ratinthorn et al 2009;Beattie et al 2010;Decker et al 2010;Mbonye et al 2012;Shannon et al 2012). Female sex workers also are at increased risk for adverse reproductive health outcomes, including sexually transmitted infections and unintended pregnancies (Swain et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Researchers suggest that female sex workers (FSWs) are a vulnerable group subject to a high risk of violence perpetrated by their sexual partners (El-Bassel, Witte, Wada, Gilbert, & Wallace, 2001; Ratinthorn, Meleis, & Sindhu, 2009). For instance, Shannon and colleagues (2009) reported that 57% of FSWs in Vancouver experienced gender-based violence at least once during their work in the past 18 months.…”
mentioning
confidence: 99%